PENGEMBANGAN SOLAR PHOTOVOLTAIC SYSTEM DENGAN MPPT UNTUK TEKNOLOGI IOT- SEMAR - Putra Asmara Danu; Erik Tridianto; Sritrusta Sukaridhoto (PROSIDING SNAST, 2018)
Photovoltaic system is one of renewable energy applied to industrial equipments and public facilities. The case study in this study was demonstrated by the design of photovoltaic systems on the Internet of Things (IoT) technology of Smart Environment Monitoring and Real Time System Analytics (SEMAR). IoT - SEMAR is designed on a ship prototype consisting of motor drives, servo motors, and raspberry pi. Photovoltaic system design process is done by considering location, electric energy consumption per day, and solar radiation with the aim of obtaining efficient design. From the calculation obtained solar photovoltaic capacity of 50 Wp / 18 V, with a storage battery of 17 Ah / 12 V. The results obtained by considering the accumulation of power consumption per day multiplied by a correction factor of 1.3. Based on the measurement, the driving force requires energy of 51 Wh, a servo motor of 1.5 Wh, and raspberry pi of 52 Wh so that the energy requirement per day is obtained by 105 Wh. For more effective electrical energy absorption, solar charge is used with Maximum Power Point Tracking (MPPT) with 5 A capacity. The test result through direct hardware application shows that the design with the addition of MPPT solar charge can produce 140 Wh / day, which is enough to operate IoT - SEMAR non-stop. This procedure is compatible for designing off-grid photovoltaic applications, particularly those located in remote locations.